SWI/SNF Component BAF250a Coordinates OCT4 and WNT Signaling Pathway to Control Cardiac Lineage Differentiation - Lei, Ienglam; Tian, Shuo; Chen, Victor; Zhao, Yong; Wang, Zhong (Frontiers in Cell and Developmental Biology, 2020)
Dissecting epigenetic mechanisms controlling early cardiac differentiation will provide insights into heart regeneration and heart disease treatment. SWI/SNF complexes remodel nucleosomes to regulate gene expression and play a key role in organogenesis. Here we reported a unique function of BAF250a in regulating the physical interaction of OCT4 and β-CATENIN during cardiac lineage differentiation from human ESCs. BAF250a deletion greatly reduced the physical interaction between OCT4 and β-CATENIN but did not alter the expression of β-CATENIN and OCT4 in the mesodermal progenitor cells. BAF250a ablation led to decreased recruitment of OCT4 and β-CATENIN at promoters of key mesodermal lineage genes, such as MESP1 and EOMES. Subsequently, the expression of lineage specific genes was down-regulated whereas the expression of pluripotent genes was up-regulated. In parallel, BAF250a ablation also altered recruitments of OCT4 and β-CATENIN to the promoter of CCND2 and CCND3, two key genes for S phase entry during cell cycle. Consequently, BAF250a deletion led to prolonged S phase in Mesp1+ cardiac progenitor cells, which in turn inhibited efficient differentiation of Mesp1+ to Isl1+ cells. Furthermore, BAF250a deletion abolished the interaction of OCT4 and BRG1 in mesoderm, suggesting that BAF250a is the key component in SWI/SNF complex that determines the interaction of Oct4/β-catenin in mesoderm. In contrast, we found that BAF250a did not regulate the OCT4/β-CATENIN interaction during neuroectoderm differentiation. Altogether, our results suggest that BAF250a specifically controls proper cardiac mesoderm differentiation by reorganizing the binding of OCT4/β-CATENIN and regulates both key lineage differentiation genes and cell cycle genes coincided in response to WNT/β-CATENIN signal.